Ainda é preciso ser cético - Porchat Pereira, Oswaldo (Praxis Filosófica, 2001)
In its first part and using contemporary philosophical language, thispaper delineates the basic outline of skeptical philosophy according toancient pyrrhonism, both in its negative, antidogmatic dialectic face, andits positive one, as a philosophy of daily, practical life. The second partis consecrated to stress the close proximity of pyrrhonism to contemporarytrends of philosophical thought and to make evident the permanentinterest of remembering again Greek skepticism.